Between Customary Justice and Criminal Accountability: Dayak Bakumpai Adat Law in Domestic Violence Resolution - Nugraha, Satriya; Ali, Nuraliah; Wulandari, Vicka Prama (Prophetic Law Review, 2025)
This study aims to analyze the role of Dayak Bakumpai’s Adat Law in resolving domestic violence (DV) cases. Dayak Bakumpai Adat Law continues to play a significant role in community life, particularly in addressing family conflicts, including DV. Although customary mechanisms are often preferred at the community level for their emphasis on deliberation, reconciliation, and social harmony, they cannot legally replace formal criminal prosecution for DV cases under Indonesian law. Therefore, this study provides a nuanced analysis to avoid implying that customary sanctions, such as fines or community service, constitute a lawful substitute for state-enforced criminal accountability. This study adopts an empirical approach, using a descriptive qualitative method that includes literature reviews and interviews with customary leaders and local community members. Data were also collected through field observations to understand the process of resolving DV cases based on Dayak Bakumpai's Adat Law mechanisms. The study results reveal that Adat Law demonstrates flexibility in handling DV cases through deliberation involving families, customary leaders, and community leaders. This customary resolution mechanism effectively maintains social harmony and prevents conflict escalation. However, the study also identifies challenges arising from inconsistencies between customary and national laws. In some cases, customary sanctions are deemed too lenient for DV perpetrators, raising concerns about the protection of victims, especially women. Still, they hold no authority to terminate or replace criminal liability. Additionally, Adat Law has not been fully recognized within Indonesia's formal legal system, leading to a duality of legal approaches in addressing DV cases. This creates a potential duality in legal approaches and underscores the need to harmonize customary practices with the national criminal justice system to safeguard victims’ rights while respecting local wisdom.